ANALISIS FAKTOR YANG MEMPENGARUHI EKSPOR VANILI INDONESIA KE PASAR AMERIKA SERIKAT DIBANDINGKAN DENGAN PESAINGNYA (MADAGASKAR DAN PRANCIS): ANALISIS FAKTOR YANG MEMPENGARUHI EKSPOR VANILI INDONESIA KE PASAR AMERIKA SERIKAT DIBANDINGKAN DENGAN PESAINGNYA (MADAGASKAR DAN PRANCIS) - Sari, Vinanda Puspita; Lestari, Retna Dewi; Sepfrian, Bimoseno (Journal Science Innovation and Technology (SINTECH), 2025)
This research aims to analyze the factors affecting the export level of Indonesian vanilla to the United States market, focusing on aspects of global competition. Several key variables analyzed in this study include price, exchange rates, and export volumes from competing countries. Madagascar and France were chosen as comparison countries because both are Indonesia's main competitors in vanilla trade in the United States market, with Madagascar being the largest vanilla producer in the world and France as an active player in the global distribution chain. Indonesia has the opportunity to become a major producer in the United States market, utilizing Indonesia's tropical climate and the distinctive characteristics of Indonesian vanilla as attractions in the global market. The United States, as a global market for vanilla, has an increasing demand value. The analysis method used is logistic regression, utilizing secondary data from 1999 to 2024. The research results show that there are two variables that significantly affect the increase in Indonesian vanilla export volume, namely the exchange rate of France against the United States dollar (USD) and the export volume of vanilla from France. Both variables have a partial effect on Indonesia's export volume, indicating that fluctuations in exchange rates and export activities of competing countries can affect Indonesia's competitiveness in the global market.